2004
DOI: 10.1002/ejoc.200400620
|View full text |Cite
|
Sign up to set email alerts
|

The Structures and Thermodynamics of Complexes between Water‐Soluble Calix[4]arenes and Dipyridinium Ions

Abstract: Three crystalline complexes were prepared by the inclusion complexation of p‐sulfonatothiacalix[4]arene (TCAS) and p‐sulfonatocalix[4]arene (CAS) with 2,2′‐dipyridinium (2‐DPD; (complexes 1 and 2, respectively), and TCAS with 4,4′‐dipyridinium (4‐DPD; complex 3). The crystal structures show that the calixarenes in 1 and 2 maintain their original cone conformation, with shallow inclusion of 2‐DPD, and assemble themselves into bi‐layer arrangements. However, the cone shape of TCAS in 3 is disrupted by 4‐DPD to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Besides strength and directionality, the defining criterion for a robust supramolecular synthon is its frequency of occurrence. Although reported few and far between, sulfonate···pyridinium interactions are not categorized as robust supramolecular synthons. , Our recent account of supramolecular assemblies based on this synthon indicated its facile manifestation . Molecular salts 1 – 6 further indicate persistent sulfonate···pyridinium synthon formation, even in the presence of other possible competing interactions.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Besides strength and directionality, the defining criterion for a robust supramolecular synthon is its frequency of occurrence. Although reported few and far between, sulfonate···pyridinium interactions are not categorized as robust supramolecular synthons. , Our recent account of supramolecular assemblies based on this synthon indicated its facile manifestation . Molecular salts 1 – 6 further indicate persistent sulfonate···pyridinium synthon formation, even in the presence of other possible competing interactions.…”
Section: Discussionmentioning
confidence: 95%
“…It was also observed that in addition to thermal and chemical stability, proton transfer leads to incipience of color in the products of colorless pristine formers. These results prompted us to further investigate the sparsely reported sulfonate···pyrdinium synthon. In addition to fewer hits than for the corresponding carboxylic acid···pyridine synthon, our CCDC search indicated a large tendency for proton transfer of the sulfonic proton to pyridyl nitrogen, i.e., salt formation in the sulfonic acid pyridine-based synthon, Chart . Here, we report a series of supramolecular aggregates utilizing aryl-sulfonic acid and various pyridyl derivatives (Chart ), as a case for consideration of sulfonate···pyridinium interaction as a robust supramolecular synthon.…”
Section: Introductionmentioning
confidence: 99%
“…209 In this case, the pyridinium cation was selectively included in the calix[4]arene's cavity. Liu et al also investigated the complexation process of bipyridinium 209,210 and biguanidinium 211 guests with calix [4]arene 69 4− in water solution.…”
Section: Covalent Receptors Possessing a Concavementioning
confidence: 99%
“…Supramolecular chemistry, defined as the chemistry of molecular assemblies, studies the structures and functions of entities consisting of two or more species linked by noncovalent bonds. Electrostatic interactions, hydrogen bonds, π-π stacking, metal-ligand, and hydrophobic interactions and stearic repulsions join in the formation of such assemblies [1][2][3][4][5]. Carbon nanotubes, CNT, are building blocks used in the construction of molecular assemblies.…”
Section: Introductionmentioning
confidence: 99%